Loss of Aerobic Respiration and Hydrocarbon Degradation Potential in Soils Acutely Contaminated with Used Vegetable Oil - Kindangen, Wulan; Mantiri, Feky; Mambu, Susan (Universitas Sam Ratulangi, 2025)
The improper disposal of waste cooking oil (WCO) presents a significant environmental issue as it can obstruct soil pores and rapidly induce anoxia. However, the genomic-scale disturbance that occurs immediately after a spill remains poorly understood. Here, we used comparative 16S rRNA metagenomics to investigate early-stage dysbiosis in tropical alluvial–regosol soils from North Sulawesi subjected to acute WCO contamination (<3 months). We observed a significant decline in alpha diversity and a fundamental restructuring of the soil microbiome, characterized by an expansion of opportunistic Proteobacteria, particularly the order Burkholderiales, displacing a diverse native flora. Importantly, predictive functional profiling using PICRUSt2 revealed a critical metabolic bottleneck: although genes associated with aromatic-compound degradation (e.g., toluene and catechol pathways) were selectively enriched, core aerobic respiration pathways were strongly suppressed, especially cytochrome c oxidase. This physiological decoupling suggests that, while indigenous “first responder” communities retain enzymatic potential to degrade pollutants, their catabolic activity is severely constrained by physical oxygen limitation. In contrast to this acute-state pattern of Proteobacterial proliferation coupled with respiratory impairment, our prior observations from chronically WCO-contaminated soils in Bitung indicate a Firmicutes-dominated endpoint consistent with a stable, fermentation-associated community under long-term oxygen limitation. Collectively, these findings highlight immediate soil aeration as a critical intervention to unlock the latent bioremediation potential of indigenous bacterial communities.